Nilai Gizi Brownis Subtitusi Tepung Kacang Hijau dengan Metode Panggang dan Kukus - Arizona Selsa Hany; Lilia Faridatul Fauziah (Yayasan Literasi Sains Indonesia, 2024)
One common health issue among adolescents, particularly teenage girls, is anemia. Anemia is a condition where the number of red blood cells or hemoglobin (Hb) is below normal, often due to a diet low in iron. Green beans, which are rich in iron, can be used as an alternative ingredient in brownies for individuals with anemia. Cooking techniques play a crucial role in preserving the nutritional content of food. In brownie preparation, the techniques used are steaming (with hot steam) and baking (with dry heat in an oven). This study employs a True Experimental Design with a Completely Randomized Design (CRD), involving 3 treatment levels, 1 control, and 6 replications. Treatments include comparisons of wheat flour to green bean flour ratios: P0 (100%:0%), P1 (75%:25%), P2 (50%:50%), P3 (25%:75%). Statistical analysis uses Kruskal-Wallis and Wilcoxon tests. The results indicate significant differences in protein, moisture, and iron content between steaming and baking techniques, but no significant differences in fat, carbohydrates, and ash content. This suggests that cooking methods affect the nutritional content and acceptability of brownies, with steamed and baked brownies showing variations in nutrient content and acceptability, particularly in protein, moisture, and iron.